2018
DOI: 10.1017/s0144686x18000843
|View full text |Cite
|
Sign up to set email alerts
|

Day centres for older people: a systematically conducted scoping review of literature about their benefits, purposes and how they are perceived

Abstract: With a policy shift towards personalisation of adult social care in England, much attention has focused on individualised support for older people with care needs. This article reports the findings of a scoping review of United Kingdom (UK) and non-UK literature, published in English from 2005-2017, about day centres for older people without dementia and highlights the gaps in evidence. This review, undertaken to inform new empirical research, covered the perceptions, benefits and purposes of day centres. Sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
99
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(113 citation statements)
references
References 113 publications
(290 reference statements)
6
99
1
7
Order By: Relevance
“…and, in the 2005-17 literature, centres were reported to be mainly used by people whose health had begun to decline (11). Further corroborating this finding was the exclusion from the present study of 41 per cent of observed attenders due to dementia-related cognitive limitations.…”
supporting
confidence: 83%
“…and, in the 2005-17 literature, centres were reported to be mainly used by people whose health had begun to decline (11). Further corroborating this finding was the exclusion from the present study of 41 per cent of observed attenders due to dementia-related cognitive limitations.…”
supporting
confidence: 83%
“…As demonstrated by two recent reviews, the existing literature has mainly focused on what happens inside the senior center but there is a lack of information about seniors' lives beyond the center [33] and more research on the individual effects of senior center attendance is needed [34]. With the notable exception of Turner et al [35], who used pedometers to measure seniors' weekly physical activity, to our knowledge no other study has used a device-based measurement of physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Commissioners and other commentators may view them as outdated, whilst simultaneously day centre attendees value the service (Orellana et al, 2018;Needham, 2014). Day centre pg.…”
Section: Discussionmentioning
confidence: 99%